Monday, October 18, 2010

INVERSE OF A FUNCTION

To find the inverse ( f^-1)(x) of a function f(x); follow the following steps:
Example: Find the inverse of
y = 1-2x

1) Write the original equation.
y = 1-2x

2) Solve it in terms of x.
y = 1 -2x
-2x = -1 + y
x = (1-y)/2

3) Interchange y and x in the result of step 2.

x = (1-y)/2 ==> y = (1-x)/2

4) The inverse function f^-1(x) of f(x) = 1 -2x
is therefore f^-1(x) = (1-x)/2


Related post



No comments:

Related Posts Plugin for WordPress, Blogger...